Real-world effectiveness of posaconazole as antifungal prophylaxis in acute myeloid leukemia patients undergoing induction chemotherapy at a referral hospital in Peru - Bazán Ruiz, Susy (2025)
Background: Invasive fungal infections (IFIs) significantly increase morbidity and mortality in patients with acute myeloid leukemia (AML) undergoing induction chemotherapy. Although posaconazole is recommended as first-line antifungal prophylaxis, real-world data from Latin American settings remain limited. Objective: To evaluate the real-world effectiveness of posaconazole as antifungal prophylaxis in AML patients receiving induction chemotherapy at a referral hospital in Lima, Peru. Materials and Methods: This retrospective observational study included 94 patients with AML who received induction chemotherapy between 2017 and 2020. The patients were divided into three groups based on the type of antifungal prophylaxis: posaconazole, fluconazole, or no prophylaxis. IFI rates were compared across groups. Results: Posaconazole prophylaxis was associated with a statistically significantly lower IFI incidence compared to than no prophylaxis (2.7% vs. 39.5%; p < 0.001). Additionally, the posaconazole group showed a lower IFI incidence compared to the fluconazole group (2.7% vs. 15.8%; p = 0.108).  Only one breakthrough fungal infection has been reported in the posaconazole group. No adverse effects attributable to posaconazole were observed. Conclusions: In this real-world setting, posaconazole was effective and well tolerated for preventing IFIs in patients with AML undergoing induction chemotherapy. These findings support its use as the preferred prophylactic strategy in Latin American settings, particularly in regions with a high burden of invasive aspergillosis.